[Memo from Caleb Marshall to Debbie Schoonmaker regarding media coverage of Minnesota CTJ Press Conference] - CALEB MARSHALL (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Memo from Caleb Marshall to Debbie Schoonmaker regarding media coverage of Minnesota CTJ Press Conference, May 10, 1989. Discusses significance of CTJ study in reference to Minnesota state tax code. Includes 3 clippings adressing effects of excise taxes on working class in Minnesota.